Electrical Energy Auditing And Enhanchment of Power System at Basbari Water Treatment Plant, Kathmandu - Dhakal, Dipesh; Bhattarai, Nawraj; Jha, Navin Kumar (Journal of Advanced College of Engineering and Management, 2023)
The water treatment plant (WTP) employs a variety of electrical machines and utilities, making it an intensive energy consumption plant. In this study, an energy audit was conducted on the Basbari WTP in Kathmandu, Nepal to identify the hotspots that consume most of the energy in the plant and recommend solutions for energy-efficient operation. A power quality analyzer was used to analyze the energy consumption patterns of electrical parameters and data from the electricity authority. The study found that transmission pumps and backwash/makeup pumps consume 77% and 6% of the energy, respectively. Efficient utilization of pump motors could result in an annual cost savings of NRS 160,954.81 from transmission pumps, backwash pumps, and make pumps. The payback period for light replacement and installation of a capacitor bank is 2.16 years and 1.95 years, respectively.